2016
DOI: 10.1186/s12974-016-0613-8
|View full text |Cite
|
Sign up to set email alerts
|

Oncostatin M promotes excitotoxicity by inhibiting glutamate uptake in astrocytes: implications in HIV-associated neurotoxicity

Abstract: BackgroundElevated levels of oncostatin M (OSM), an interleukin-6 cytokine family member, have been observed in HIV-1-associated neurocognitive disorders (HAND) and Alzheimer’s disease. However, the function of OSM in these disease conditions is unclear. Since deficient glutamate uptake by astrocytes is instrumental in HAND-associated neurotoxicity, we hypothesized that OSM impairs glutamate uptake in astrocytes and thereby promotes neuronal excitotoxicity.MethodsPrimary cultures of mouse cortical astrocytes, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 76 publications
0
32
0
Order By: Relevance
“…Pro‐survival JAK2/STAT3 cascade is localized primarily within astrocytic nuclei (Oliva, Kang, Sanchez‐Molano, Furones, & Atkins, ). This cascade is responsible for the activation of GFAP gene by many factors, such as cholera toxin and interleukin (IL)‐6 in C6 malignant glioma cells (Shu et al, ), oncostatin M (OSM) in cortical neurons (Moidunny et al, ), epidermal growth factor in human glioblastoma (He et al, ), and IL‐33 in spinal glia (Du et al, ). In contrast, the inhibition of astrocyte proliferation and GFAP expression is due to suppression of JAK2/STAT3 pathway by some other factors, such as sevoflurane in the hippocampus of neonatal rats (Wang, Lu, Feng, & Zhang, ), oleanolic acid in neural stem cells (Zhang et al, ), and SN79 in striatum in mice (Robson et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
See 1 more Smart Citation
“…Pro‐survival JAK2/STAT3 cascade is localized primarily within astrocytic nuclei (Oliva, Kang, Sanchez‐Molano, Furones, & Atkins, ). This cascade is responsible for the activation of GFAP gene by many factors, such as cholera toxin and interleukin (IL)‐6 in C6 malignant glioma cells (Shu et al, ), oncostatin M (OSM) in cortical neurons (Moidunny et al, ), epidermal growth factor in human glioblastoma (He et al, ), and IL‐33 in spinal glia (Du et al, ). In contrast, the inhibition of astrocyte proliferation and GFAP expression is due to suppression of JAK2/STAT3 pathway by some other factors, such as sevoflurane in the hippocampus of neonatal rats (Wang, Lu, Feng, & Zhang, ), oleanolic acid in neural stem cells (Zhang et al, ), and SN79 in striatum in mice (Robson et al, ).…”
Section: Expression Of Gfap and Its Regulationmentioning
confidence: 99%
“…Pro-survival JAK2/STAT3 cascade is localized primarily within astrocytic nuclei (Oliva, Kang, Sanchez-Molano, Furones, & Atkins, 2012). This cascade is responsible for the activation of GFAP gene by many factors, such as cholera toxin and interleukin (IL)-6 in C6 malignant glioma cells (Shu et al, 2011), oncostatin M (OSM) in cortical neurons (Moidunny et al, 2016), epidermal growth factor in human glioblastoma (He et al, 2013), and IL-33 in spinal glia (Du et al, 2019).…”
Section: Jak2/stat3 Cascadementioning
confidence: 99%
“…Although the FCs of the pSTAT3 + /S100b + astrocytes were increased even more in 15-and 21-week-old SOD1 G93A mice, our findings suggested that astrocytic STAT3 was activated in the SOD1 G93A mice in the presymptomatic stage by a mechanism that was developed independently of axonal impairment and neuroinflammation. In this regard, an interesting study has shown that the activation of astrocytic STAT3 impairs the ability of astrocytes to remove glutamate from the extracellular space, which contributes to excitotoxic neuronal damage (Moidunny et al, 2016). Although future studies are needed, these findings suggest that the activation of astrocytic STAT3 may increase the glutamate toxicity that occurs in the early stages of ALS (van Zundert et al, 2012).…”
Section: Activation Of Stat3 In Astrocytesmentioning
confidence: 99%
“…This concentration of EcoHIV was based on previous studies using a comparable concentration in a similar in vitro system to induce an inflammatory response. 43 Exposure of the cells to EcoHIV significantly increased the inflammatory markers TNFα, IL-1β, IL-6, CCL2, CCL3, CXCL10, and C3; at 24-h post-EcoHIV exposure (Figure 1). Previous studies from our laboratory have shown that exposure to full PPARγ agonists (rosiglitazone or pioglitazone) reversed HIV-1 envelope gp120 or EcoHIV induced mRNA expression of pro-inflammatory cytokines and oxidative stress markers in primary cultures of mixed rodent astrocytes and microglia.…”
Section: Int131 Mitigates Ecohiv-mediated Inflammatory Responses Inmentioning
confidence: 94%
“…EcoHIV is a robust rodent model to investigate HIV-related brain pathologies, we and others have demonstrated that infection of mice leads to neuroinflammation and neurocognitive impairments. 34,42,43 We assessed the effect of INT131 treatment on the expression of inflammatory markers in vitro, utilizing primary cultures of mouse mixed glial cells exposed to EcoHIV, and in vivo, in mice intracranially injected with EcoHIV. Additionally, we conducted a pharmacokinetic (PK) study to characterize INT131 brain tissue penetration.…”
Section: Introductionmentioning
confidence: 99%